New Approaches to Studying Silent Mesial Temporal Lobe Seizures in Alzheimer's Disease - Lam, Alice D.; Cole, Andrew J.; Cash, Sydney S. (Frontiers in Neurology, 2019)
Silent seizures were discovered in mouse models of Alzheimer’s disease over 10 years ago, yet it remains unclear whether these seizures are a salient feature of Alzheimer’s disease in humans. Seizures that arise early in the course of Alzheimer’s disease most likely originate from the mesial temporal lobe, one of the first structures affected by Alzheimer’s disease pathology and one of the most epileptogenic regions of the brain. Several factors greatly limit our ability to identify mesial temporal lobe seizures in patients with Alzheimer’s disease, however. First, mesial temporal lobe seizures can be difficult to recognize clinically, as their accompanying symptoms are often subtle or even non-existent. Second, electrical activity arising from the mesial temporal lobe is largely invisible on the scalp electroencephalogram (EEG), the mainstay of diagnosis for epilepsy in this population. In this review, we will describe two new approaches being used to study silent mesial temporal lobe seizures in Alzheimer’s disease. We will first describe the methodology and application of foramen ovale electrodes, which captured the first recordings of silent mesial temporal lobe seizures in humans with Alzheimer’s disease. We will then describe machine learning approaches being developed to non-invasively identify silent mesial temporal lobe seizures on scalp EEG. Both of these tools have the potential to elucidate the role of silent seizures in humans with Alzheimer’s disease, which could have important implications for early diagnosis, prognostication, and development of targeted therapies for this population.